Electrical stimulation promotes regeneration and re-myelination of axons of injured facial nerve in rats. (4th March 2018) - Deng, Yue; Xu, Yaping; Liu, Huanhai; Peng, Hu; Tao, Qilei; Liu, Hongyi; Liu, Haibin; Wu, Jian; Chen, Xiaoping; Fan, Jingping
Abstract: Objective: To investigate the effects of electrical stimulation (ES) on the nerve regeneration and functional recovery of facial expression muscles in facial nerve defect rats. Methods: Sixty rats were surgically introduced with a 1-cm defect on the right facial nerves and evenly divided into the Surgery group (Group A, the main trunk of the right facial nerve was surgically cut-off with a 1.0 cm at the foramina stylomastoideum) and the Surgery + ES group (Group B). Twenty normal rats were as normal control group (without receiving surgery or ES). For rats in group B, the orbicularis oris muscle of the right paralyzed face was stimulated with an electrical pulse of 3 V, 20 Hz and 0.3 mA for 1 h each day. The effects of ES on the facial muscle movement, compound muscle action potentials (CMAPs), histological structure, and the expression levels of S100B and NF200 proteins were comparatively studied. Results: In group A, facial paralysis scores were slightly improved from day 1 to 28; the facial nerve trunks had swelled and malformed till day 14; and CMAPs could be induced in fewer animals and were abnormal, resulting in a slow recovery of the facial muscle movement. In group B, facial paralysis scores were improved from 4 to 2.6 during the 4 weeks; more rats showed a higher amplitude and shorter latency of CMAPs from day 14 to 28 after surgery; and increased axons and the expression of S100B and NF200 proteins and gradually decreased swelling in the injured facial nerve. Conclusion: ES promotes outgrowth and myelination of axons and a partial functional recovery of facial muscles in injured facial nerve rats.